2012
DOI: 10.3233/jad-2012-112183
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Transcripts Related to Alzheimer's Disease in a Model of HFE Hemochromatosis are not Consistent with Increased Alzheimer's Disease Risk

Abstract: Iron abnormalities are observed in the brains of Alzheimer's disease (AD) patients, but it is unclear whether common disorders of systemic iron overload such as hemochromatosis alter risks of AD. We used microarrays and real-time reverse transcription-PCR to investigate changes in the brain transcriptome of adult Hfe-/- mice, a model of hemochromatosis, relative to age- and gender-matched wildtype controls. Classification by functional pathway analysis revealed transcript changes for various genes important in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 82 publications
(89 reference statements)
1
12
0
Order By: Relevance
“…A number of key genes identified in our previously published transcriptomic studies of the Hfe -/-mouse model of hemochromatosis (Johnstone et al, 2012a;Johnstone et al, 2012b) also showed expression changes in the Tfr2 mut mouse model, validating our previous findings and providing support for the assertion that disruption of iron homeostasis can lead to important changes in the brain. These include effects on genes involved in long-term depression, a molecular pathway that was significantly enriched among down-regulated transcripts in the two models.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…A number of key genes identified in our previously published transcriptomic studies of the Hfe -/-mouse model of hemochromatosis (Johnstone et al, 2012a;Johnstone et al, 2012b) also showed expression changes in the Tfr2 mut mouse model, validating our previous findings and providing support for the assertion that disruption of iron homeostasis can lead to important changes in the brain. These include effects on genes involved in long-term depression, a molecular pathway that was significantly enriched among down-regulated transcripts in the two models.…”
Section: Discussionsupporting
confidence: 73%
“…The list of downregulated genes classified in these pathways is given in Table 3. Notably, the long-term depression pathway was also identified as down-regulated in our previous study of Hfe -/-mouse brain (Johnstone et al, 2012b). …”
Section: Pathway Enrichment Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…42) Relative changes in gene expression were determined using ΔΔCt method, and β-actin was used as the internal control. 43,44) Western Blotting Analysis Samples were prepared from NSCs after Ost treatment for 3 d, or from brain hippocampus of the mice treated with Ost for 6 weeks. The Western blotting was performed as previously described.…”
Section: Preparation Of Ostmentioning
confidence: 99%